Digital Financial Literacy and Behaviour: Exploring the Mediating Effect of Financial Confidence among University Students in Nepal (KMC Journal, 2025)
The instrumental and behavioural growth should be parallelized to establish the fintech ecosystem. This study examines the relationship between digital financial literacy, confidence, and behaviour among university-level students. Additionally, the study investigates the mediating effect of financial confidence on the relationship between digital financial literacy and financial behaviour. A causal-comparative study design was employed to collect primary data from 404 university students in the Kapilvastu district, who were pursuing bachelor’s and master’s degrees in management, through a purposeful, closed-ended, structured questionnaire survey. The research framework and instruments used to measure variables were based on literature. Structural equation modeling (SEM), including EFA, CFA, Path analysis, and mediating effects, was used to analyze the data and identify a significant relationship between digital financial literacy, confidence, and behaviour among university students. Moreover, there was a significant mediating role of financial confidence. Higher digital financial literacy and confidence demonstrated greater proficiency in navigating digital financial platforms and were more likely to exhibit sound financial behaviour. The study suggests that national education and financial inclusion efforts should give more attention to including digital financial literacy. Improving access to digital financial literacy and user confidence leads to financial behaviour in a well-equipped and skilled financial digital ecosystem.